CREATIVE LANGUAGE USE IN THE MOTHER TONGUE: A CASE STUDY OF A FOUR-YEAR-OLD INDONESIAN CHILD IN THE FAMILY SETTING - Dwie Agustiani, Indah Windra; Rafli, Zainal; Boeraswati, Endry (English Community Journal, 2025)
Language acquisition is  the process of acquiring the mother tongue, beginning with crying, cooing, and babbling, and eventually progressing to speaking. Between the ages of two and four, children demonstrate a noticeable development of language creativity. This study aims to provide example of  the evidence of language creativity of a four year old Indonesian child. This research is  a  qualitative method with case study approach. The subject of this research is a four year old Indonesia child. The data were collected through observation and note-taking, and then analysed descriptively to draw conclusions.The result of the observation in this study revealed 17 utterances that serve as evidence of the child’s language creativity. The result of this study can be concluded that childish creativity in language acquisition  is a kind of  speaking ability of  a child for overcoming his/her limitation for words they still do not have to describe  new things then, he made the mistake when he independently try to  use his  language. As for the creative use of language, based on the data of this research, it  can be caused by the child’ syntactical problem: misuse of adjective to make adverb,  time concept confusion, semantical problems: failure to combine nouns with correct adjectives to make the opposition of particular  words and morphological problems :the use of suffix for words to form verbs, which are caused the  absence of  dictions  to describe new things   but  his intended meanings can be easily understood. It also happened because of generalization  made by the child in order to overcome his limitation in speaking result in  improper word selection.